Fortune-Yankelovich Youth Study, 1966 ([Verlag nicht ermittelbar], 1984)
This survey of American youth of college age, including both college students and non-students, was conducted in 1968 by Daniel Yankelovich, Inc., for Fortune Magazine. The questions explored a wide range of issues reflecting personal values, career goals, and social and political philosophies. Among the major topics investigated were the respondents' opinions on the draft, civil disobedience, student riots, science and technology, and the generation gap. In addition, respondents were asked to compare their values with those of their parents, and to indicate societal values that they would adhere to, or reject. Demographic variables include sex, age, marital status, occupation, and income.